Kolaborasi Stakeholder Dalam Pengembangan Wisata Religi Di Kota Tangerang : Studi Kasus Festival Masjid Raya Al-Azhom Tahun 2022 - Alifia Nur Ramadhani; Irvan Arif Kurniawan; Eko Prasetyo (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
The results of the research show that the process of collaboration between stakeholders is running quite well, although not perfect overall in terms of collaboration. The government's collaboration through the Youth and Sports Service with a religious organization, namely BKPRMI, has collaborated regarding the Al-Azhom Festival activities starting in 2012, budget constraints and limited human resources in carrying out Al-Azhom Festival activities can be overcome by collaboration between stakeholders, and not only Meanwhile, UMKM and the people of Tangerang City also participate in the success of these religious tourism development activities. The achievements of the 2022 Al-Azhom Festival are in accordance with its objectives, namely increasing the economy of the people of Tangerang City through UMKM in the activity bazaar, and being able to introduce religious tourism in Tangerang City to the wider community.